Effect of Aspirin vs Placebo on the Prevention of Depression in Older People: A Randomized Clinical Trial - Berk, M.; Berk, M.; Woods, R.L.; Nelson, M.R.; Shah, R.C.; Reid, C.M.; Reid, Christopher; Storey, E.; Fitzgerald, S.; Lockery, J.E.; Wolfe, R.; Mohebbi, M.; et al. (2020)
© 2020 American Medical Association. All rights reserved. Importance: Depression is associated with increased inflammation, which may precede its onset, especially in older people. Some preclinical data suggest potential antidepressant effects of aspirin, supported by limited observational data suggesting lower rates of depression in individuals treated with aspirin. There currently appears to be no evidence-based pharmacotherapies for the primary prevention of depression. Objective: To determine whether low-dose aspirin (100 mg) reduces the risk of depression in healthy older adults. Design, Setting, and Participants: This double-blinded, placebo-controlled randomized clinical trial was a substudy of the Aspirin in Reducing Events in the Elderly (ASPREE) trial, which examined if aspirin increased healthy life span, defined as survival free of dementia and disability. The prespecified secondary outcome was depression. Individuals of all races/ethnicities older than 70 years in Australia, as well as white individuals older than 70 years and black and Hispanic individuals older than 65 years in the United States, were included. Interventions: Participants were randomized to aspirin (100 mg daily) or placebo, with a median (interquartile range) follow-up of 4.7 (3.5-5.6) years. Main Outcomes and Measures: The primary outcome was a proxy measure of major depressive disorder defined as a score of 8 or more on the Center for Epidemiologic Studies Depression 10-item (CES-D-10) scale. Results: Of the 19114 participants enrolled in the trial, 9525 received aspirin and 9589 received a placebo. The mean (SD) age was 75.2 (4.0) years in the aspirin group and 75.1 (4.5) years in the placebo group; 9531 (56.4%) were women. Participants' demographics and clinical characteristics at baseline were similar between groups. A total of 79886 annual CES-D-10 measurements were taken, with a mean of 4.2 measurements per participant. There were no significant differences at annual visits in the proportions of CES-D-10 scores of 8 or more between the aspirin and placebo groups. The incidence rate of new CES-D-10 scores of 8 or more was 70.4 events per 1000 person-years in the aspirin group and 69.1 in the placebo group (hazard ratio, 1.02 [95% CI, 0.96-1.08]; P =.54). Conclusions and Relevance: Low-dose aspirin did not prevent depression in this large-scale study of otherwise healthy older adults. Trial Registration: ClinicalTrials.gov Identifier: NCT01038583.